Pencabutan Hak Politik Mantan Narapidana (Studia Atas Jabatan Ketua Umum Partai Politik Anas Urbaningrum) - Azimatu Anjeli; Jamaludin Ghafur (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
Revocation of political rights is an additional form of punishment given to former convicts. The form of revocation given is usually in the form of revocation of political rights to be elected to public office. Anas Urbaningrum is one of the former convicts who received an additional sentence in the form of revocation of the right to be elected to public office for 5 (five) years from the completion of the main sentence. However, Anas Urbaningrum now serves as General Chair of a Political Party. The main issues that will be reviewed in this research are related to how the concept of revocation of political rights is applied in Indonesia and related to whether Anas Urbaningrum, whose political rights have been revoked by the court, can occupy the position of general chairman of a political party or not. This research is normative legal research using statutory, conceptual and case approach methods. The research results state that political rights that can be revoked according to the Criminal Code are the right to hold office in general or certain positions as well as the right to vote and be elected in elections held based on general rules. Positions in general and certain positions have general meanings. The implementation of the revocation of Anas Urbaningrum's political rights should have a 5 (five) year hiatus from holding public office. The meaning of the right to be elected to public office in the Anas Urbaningrum decision, namely Supreme Court Decision Number 246 PK/Pid.Sus/2018, has a general meaning. Political parties are public bodies because their functions and objectives are related to the public interest. Thus, Anas Urbaningrum should not be able to hold the position as General Chair of a Political Party.